Can Brief Cognitive or Medication Management Tasks Identify the Potential for Dependence in Instrumental Activities of Daily Living? - Marks, Timothy S.; Giles, Gordon M.; Al-Heizan, Muhammad O.; Edwards, Dorothy F. (Frontiers in Aging Neuroscience, 2020)
Background and Objectives: The identification of functional performance deficits is critical to the community independence of older adults. We examined whether a combined cognitive and performance-based medication management measure would be able to better classify an individual’s functional cognitive status and potential for instrumental activities of daily living (IADL) impairment than either measures alone. Research Design and Methods: Community dwelling adults age 55 and older (n = 185) were administered the Mini-Cog, the Medication Transfer Screen-Revised (MTS-R), a combination measure the Medi-Cog-Revised (Medi-Cog-R), the Performance Assessment of Self-Care Skills (PASS) Checkbook Balancing and Shopping tasks (PCST), additional cognitive screening measures, and a self-report daily living scale. Receiver operating characteristic (ROC) curve analyses were computed for the Mini-Cog, MTS-R and the Medi-Cog-R using the PCST subtest performance as the criterion measure. Area under the curve (AUC), sensitivity, and specificity were computed for each measure. Results: The Medi-Cog-R most accurately identified individuals as impaired on the PCST subtests. An AUC statistic of .82 for the Medi-Cog-R was greater than either the Mini-Cog (.75) or the MTS-R (.73). The Medi-Cog-R demonstrated a sensitivity of .71 and a specificity of .78 in classifying individuals with impaired IADL. Discussion and Implications: The Mini-Cog, the MTS-R, and the Medi-Cog-R all show discriminant validity, but the combined measure demonstrates greater sensitivity and specificity than either component measure alone in identifying IADL impairment. The Medi-Cog-R appears to be a useful screening measure for functional cognition and can be used to prompt further assessment and intervention to promote community independence.